PRIMING MAIZE (Z ea mays) S EED WITH PHOSPHATE SOLUTIONS IMPROVES SEEDLING GROWTH AND YIELD - G. Miraj; H. U. Shah; M. Arif (Journal of Animal and Plant Sciences, 2013)
In this study field experiments were conducted to assess the effect of different phosphorus priming sources on seedling growth and yield of maize cv. Azam at two locations i.e. The University of Agriculture and Agricultural Research Institute, Peshawar, Khyber Phukhtunkhwa, Pakistan during 2008 and 2009. Phosphorus concentration (1% P), using potassium dihydrogen phosphate (KH2PO4), single super phosphate (SSP) and di-ammonium phosphate (DAP) along with amended solutions of SSP (20 g l-1 KOH, 15 g l-1 NaOH and 12.5 g l-1 Na2CO3) were included in the experiment. Water primed and non primed seeds were also used as controls. Seeds were primed for 16 h and were then air-dried for 30 minutes. They were sown in mini plots and in the field. Seedlings were cut at 21 days old stage and remaining field plants were harvested after maturity. Three weeks old mini plots and field seedlings grown from seeds primed with water, P or P amended solutions showed higher vigor than unprimed seeds as reflected in increased fresh and dry shoot weights, fresh shoot height and shoot P content. Additionally the nutrient uptake of seedling was increased four times due to 1 % P solution priming with KH2PO4. Yield of maize was also increased in response to P priming showing significant results in cobs yield, grain and straw yields. Phosphorus content of grain was also enhanced as compared to control. Priming maize with SSP + 20 g l-1 KOH showed almost the same effect as that of KH2PO4. From the experiment it is concluded that priming maize seeds with SSP + 20 g l-1 KOH is more effective alternate than KH2PO4 as SSP is generally used fertilizer and KOH is also easily available in market. Thus KOH + SSP would be an easier and cheaper available source of P for the poor farmer.
Keywords: maize; phosphorus priming sources; potassium hydroxide; single superphosphate; sodium carbonate; sodium hydroxide; yield